Effect of consumption value on green purchase intention of organic food: The mediation role of attitude and green trust - Athisya Putri Nadifa; Sri Rahayu Hijrah Hati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
In recent years, customer interest in environmentally friendly products has been increasing, especially in organic products. In Indonesia, awareness of organic food products has started to appear since 2014. This study analyzed the influencing of consumption values on organic food green purchase. Moreover, the consumption values analyzed in this research includes conditional values, emotional values, functional values and social values. Moreover, this research also analyzed the mediating role of attitude and green trust. This research is a single quantitative cross-sectional study with a total of 265 respondents. In addition, the data was processed using SmartPLS 3.2.9 with the PLS-SEM method. The results of this study indicate that functional values and emotional values can influence green purchase intention. Meanwhile, attitude have the ability to mediate the relationship between all four consumption values and green purchase intention. The result of this study provides organizations, entrepreneur, and the government with information regarding green consumption that can be used to develop strategies and approaches to enhance consumer’s organic food buying intention. Moreover, marketers should utilize functional benefits and emotional benefits, as well as benefiting from customer’s positive attitude towards organic food purchases.